Rare earth hydrogen storage alloy and preparation method and application thereof
By using antimony atom coating on the surface of the rare earth hydrogen storage alloy, the problem of poor discharge performance of the AB5 type hydrogen storage alloy under low temperature conditions is solved, and higher cycle stability and low temperature discharge capacity are achieved.
Patent Information
- Application Number
- CN202411946841.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The poor discharge performance of the existing AB5 rare earth hydrogen storage alloy under low temperature conditions affects its efficiency in the negative electrode of nickel-hydrogen battery.
By partially displacing nickel atoms on the surface of the rare earth hydrogen storage alloy and forming in situ coating, the antimony atom-coated rare earth hydrogen storage alloy negative electrode for nickel-hydrogen batteries was prepared.
This method effectively alleviates the powdering of hydrogen storage alloy materials, improves cycle stability, and significantly improves the low-temperature discharge capacity by broadening the transmission channel of hydrogen atoms, especially at -40°C.
Smart Images

Figure CN119703068A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a rare earth hydrogen storage alloy and a preparation method and application thereof, belonging to the technical field of hydrogen storage alloy negative electrode for nickel-hydrogen battery and preparation thereof. Background Art
[0002] As the main negative electrode material of nickel-hydrogen batteries, rare earth hydrogen storage alloys have the advantages of excellent wide temperature performance, no memory effect, good kinetic performance, environmental friendliness, and high safety. They are widely used in military equipment, large-scale energy storage power stations, ice and snow industries, etc. At present, the hydrogen storage alloy materials used for the negative electrode of nickel-hydrogen batteries mainly include AB5, A2B, AB2, A2B7 and vanadium-based solid solution materials. Among them, AB5 has been successfully commercialized, and other types of hydrogen storage alloy negative electrode materials for nickel-hydrogen batteries have also made great research progress.
[0003] In order to further promote the faster and better commercial application of hydrogen storage alloy materials, researchers have adopted many new technologies and methods to improve the comprehensive performance of hydrogen storage alloys, especially the low-temperature discharge performance. Common methods for optimizing alloy systems include element substitution in alloys, preparation of composite alloys, regulation of heat treatment systems to control alloy composition, improvement of material performance, and use of common ion effects to improve the distribution of key ions in the double layer in the anode region. In addition, the surface composition, microstructure, and electrocatalytic activity of the alloy have an important influence on the low-temperature performance of nickel-hydrogen batteries. Through surface coating modification treatment, the surface properties of the alloy can be changed, the low-temperature performance of the alloy electrode can be improved, and its promotion and application process can be accelerated.
[0004] The surface modification treatment of hydrogen storage alloy electrode materials is to effectively change the surface state of hydrogen storage alloys without changing the overall properties of the original hydrogen storage alloys or fine-tuning the alloy composition, thereby improving the electrochemical and kinetic properties of hydrogen storage alloys. Commonly used alloy surface modification treatment methods include: surface coating metal film treatment, alkaline and acidic solution treatment, surface polymer modification and other methods. The above methods can effectively regulate the diffusion of H2, prevent material shedding, improve utilization, improve the cycle stability and low temperature performance of nickel-hydrogen battery negative electrode materials, thereby achieving the goal of its commercial application. For example: Patent CN115815591A mixes hydrogen storage alloys with alkaline solutions for reaction, adds water for washing after the reaction, and adds acetic acid solution to further react with the alloy to complete the surface treatment of hydrogen storage alloys. The invention adopts an alkali-acid composite treatment method to make up for the problem of alloy capacity reduction caused by a single alkali treatment process and the problem of low alloy cycle stability caused by a single acid treatment process; while ensuring the discharge capacity of the alloy, a highly activated surface state is obtained. Through the surface treatment method of the invention, the low-temperature performance deficiency of the high-capacity A2B7 type hydrogen storage alloy is compensated. At the same time, the saturation magnetization of the alloy is increased from less than 0.1emu / g of the initial alloy to 0.5-2.5emu / g, which greatly improves the metallic Ni content on the surface of the alloy. Patent CN107164657A obtains a method for preparing a graphene / La-Fe-B low-temperature hydrogen storage alloy composite material, which mainly includes the following steps: (1) preparing graphene, using an improved hummers method, mixing graphite powder: NaNO3: KMnO4: concentrated sulfuric acid in a mass percentage of 1:1-2:6-8:87-97, adding HCl after reaction, aging, removing impurities, washing, filtering, and microwave for 1 minute; (2) preparing alloy powder, placing La, Fe, Ni, Mn, B, and Al in a smelting furnace according to the corresponding ratio, and using a conventional smelting method to prepare a La-Fe-B low-temperature hydrogen storage alloy composite material with uniform composition. 15 Fe2Ni 72 Mn7B2Al2 alloy ingot is naturally cooled and crushed; (3) the graphene and alloy powder are ball-milled for 1 hour in a ratio of 1 to 5:95 to 99 by mass percentage of graphene to alloy powder to obtain a graphene / La-Fe-B low-temperature hydrogen storage alloy composite material. The low-temperature hydrogen storage alloy composite material prepared by the present invention can still maintain good discharge performance under low temperature conditions. Although the above methods all achieve the improvement of the discharge performance of the low-temperature hydrogen storage alloy composite material under low temperature conditions, the preparation method is very cumbersome and is not conducive to industrial production.
[0005] Based on the above foundation, how to further find new coating agents and coating methods with more advantages than disadvantages without changing the existing AB5 type Mm-Ni based rare earth hydrogen storage alloy material production process and equipment is very attractive to battery companies and hydrogen storage alloy powder manufacturers using AB5 type hydrogen storage alloy. Summary of the invention
[0006] In order to solve the problem that the existing AB5 type hydrogen storage alloy has poor discharge performance under low temperature conditions when used in the negative electrode of a nickel-hydrogen battery, the present invention provides a rare earth hydrogen storage alloy and a preparation method and application thereof.
[0007] The technical solution of the present invention:
[0008] One of the purposes of the present invention is to provide a method for preparing a rare earth hydrogen storage alloy, the method comprising the following steps:
[0009] (1) dispersing Mm-Ni based rare earth hydrogen storage alloy particles in ethanol and stirring uniformly to obtain a mixed turbid liquid;
[0010] (2) Antimony trichloride is dissolved in the mixed turbid liquid, and the mixture is allowed to stand after continuous stirring to obtain a mixture, which is then centrifuged, washed and vacuum dried in sequence to obtain an antimony atom-coated rare earth hydrogen storage alloy electrode.
[0011] It is further defined that the particle size of the Mm-Ni based rare earth hydrogen storage alloy particles in (1) is 200-400 mesh.
[0012] It is further defined that the Mm-Ni based rare earth hydrogen storage alloy in (1) is MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 .
[0013] Further limiting, MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 The Mm is composed of La and Ce in an atomic ratio of 0.78-0.84:0.18-0.30.
[0014] It is further defined that the concentration of antimony trichloride in the mixture obtained in (2) is 0.01 to 1 mol / L.
[0015] It is further defined that the mass ratio of antimony trichloride to Mm-Ni based rare earth hydrogen storage alloy in the mixture obtained in (2) is 0.1-1:1-4.
[0016] It is further defined that the stirring time in (2) is 10 to 48 hours and the standing time is 5 to 10 minutes.
[0017] It is further defined that the washing solvent in (2) is deionized water and ethanol.
[0018] It is further defined that the vacuum drying temperature in (2) is 40 to 60° C. and the insulation time is 5 to 15 hours.
[0019] The second object of the present invention is to provide a rare earth hydrogen storage alloy prepared by the above method.
[0020] The third object of the present invention is to provide an application of the rare earth hydrogen storage alloy, specifically, to use it as a hydrogen storage alloy negative electrode for a nickel-hydrogen battery.
[0021] Beneficial effects of the present invention:
[0022] The present invention partially replaces nickel atoms on the surface of the rare earth hydrogen storage alloy through a liquid phase reaction and forms an in-situ coating, and then obtains an antimony atom-coated rare earth hydrogen storage alloy negative electrode for a nickel-hydrogen battery, which can effectively alleviate the pulverization of the Mm-Ni-based rare earth hydrogen storage alloy material and improve the cycle stability of the hydrogen storage alloy negative electrode. At the same time, after the nickel atoms on the surface of the rare earth hydrogen storage alloy are replaced and dissolved in the solution, micropores are formed at this position, which broadens the transmission channel of hydrogen atoms. And by utilizing the "thermal shrinkage and cold expansion" property of metal antimony, the specific surface area and pore size of the hydrogen storage alloy can be effectively improved at low temperatures, thereby optimizing the performance of the hydrogen storage alloy and improving its low-temperature discharge capacity. The test results show that the antimony atom-coated nickel-hydrogen battery hydrogen storage alloy negative electrode obtained by the present invention maintains the structure of the alloy well, and the antimony atoms are uniformly coated on the alloy surface, so that the prepared Mm-Ni-based rare earth hydrogen storage alloy material with antimony atoms coated on the surface has a discharge capacity of 173mAh g at a rate of 0.2C at -40°C. -1 , showing excellent low-temperature discharge performance.
[0023] In addition, the preparation method of the hydrogen storage alloy negative electrode material for nickel-hydrogen batteries provided by the present invention is simple and easy to operate, and has excellent low-temperature discharge performance, can be widely used in nickel-hydrogen battery negative electrode materials, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 (Blank alloy) SEM image of rare earth hydrogen storage alloy;
[0025] Figure 2 This is a SEM photo of the blank alloy @Sb-1 rare earth hydrogen storage alloy material prepared in Example 1;
[0026] Figure 3This is a SEM photo of the blank alloy @Sb-2 rare earth hydrogen storage alloy material prepared in Example 2;
[0027] Figure 4 This is the distribution diagram of antimony element in the blank alloy @Sb-1 rare earth hydrogen storage alloy material prepared in Example 1;
[0028] Figure 5 A comparison diagram of X-ray photoelectron spectra of the rare earth hydrogen storage alloy materials prepared in Example 1 and Example 2;
[0029] Figure 6 This is a comparison chart of the discharge performance curves of the batteries prepared in Example 1, Example 2 and Comparative Example 1 at -40°C and 0.2C rate. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0032] Example 1
[0033] (1) MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 The rare earth hydrogen storage alloy material (wherein Mm is composed of La and Ce in an atomic ratio of 0.83:0.2) is fully ground and sieved in a mortar to select alloy powder with a particle size of 200-400 meshes.
[0034] (2) Weigh 1g MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 Rare earth hydrogen storage alloy material and 0.3 g antimony trichloride were dissolved in 100 mL ethanol solvent, stirred for 24 h to obtain a mixed solution, allowed to stand for 5 min and then centrifuged, washed three times with deionized water and anhydrous ethanol respectively, and placed in a vacuum drying oven at 60 ° C for 12 h to finally obtain an antimony atom-coated rare earth hydrogen storage alloy negative electrode material for nickel-hydrogen batteries, named blank alloy @Sb-1.
[0035] (3) Blank alloy @Sb-1 and carbonyl nickel powder were mixed in a mass ratio of 1:4 and pressed into tablets under 15 MPa. The tabs were wrapped with foamed nickel and welded to obtain a negative electrode with an active material loading of about 100 mg.
[0036] (4) A battery was prepared using the negative electrode obtained in step (3), wherein the positive electrode was sintered α-nickel hydroxide, a sulfonated polypropylene grafted membrane was used as a separator, and the electrolyte was 7.5 M KOH solution. A low-temperature discharge performance test was performed at -40°C.
[0037] Example 2
[0038] The difference between this embodiment and embodiment 1 is that the amount of antimony trichloride used in (2) is 0.4 g, and the remaining process steps and parameter settings are the same as those in embodiment 1. The final antimony atom-coated rare earth hydrogen storage alloy negative electrode material for nickel-hydrogen battery is named blank alloy @Sb-2.
[0039] Comparative Example 1
[0040] The difference between this embodiment and embodiment 1 is that: MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 The rare earth hydrogen storage alloy powder is not treated in any way and is named blank alloy. 4.7 Co 0.12 Mn 0.2 Al 0.3 Rare earth hydrogen storage alloy is used as the negative electrode active material to prepare a negative electrode with an active material loading of about 100 mg.
[0041] Application Examples
[0042] (1) The blank alloys @Sb-1 and @Sb-2 prepared in Examples 1 and 2, respectively, and the blank alloy of Comparative Example 1 were characterized by microscopic morphology. The results are as follows: Figures 1 to 3 As shown. Figure 1 It can be seen that the surface of the blank alloy is relatively smooth. Figure 2 As shown, the surface of the blank alloy @Sb-1 prepared in Example 1 is evenly coated compared to the surface of the blank alloy. And further according to the antimony element spectrum test results Figure 4 It can be seen that the antimony element is evenly distributed on its surface, that is, Example 1 prepared a hydrogen storage alloy for nickel-hydrogen batteries that is evenly coated with antimony atoms. Figure 3 As shown, the surface of the blank alloy @Sb-2 prepared in Example 2 is uniformly coated with antimony atoms.
[0043] (2) The surface element composition of the rare earth hydrogen storage alloys prepared in Example 1 and Example 2 was characterized by X-ray photoelectron spectroscopy. The results are as follows: Figure 5 As shown by Figure 5 It can be seen that the main body of antimony element exists in the form of a single substance, and only a very small amount exists in the form of oxides, which is mainly due to the adsorption of oxygen in the air.
[0044] (3) The low-temperature discharge performance test of the batteries assembled in Example 1, Example 2 and Comparative Example 1 was performed at -40°C. After activation at 0.2C rate, the batteries were fully charged. The low-temperature discharge performance at 0.2C rate at -40°C was as follows: Figure 6 As shown in the figure, the low-temperature discharge capacity of the negative electrode active materials provided in Example 1 and Example 2 and Comparative Example 1 in the rare earth hydrogen storage alloy material at a rate of 0.2C is 123 mAh g -1 , 173mAh g -1 and 146mAh g -1 .
[0045] The above results show that the antimony atom-coated MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 The cyclic stability of rare earth hydrogen storage alloy materials is significantly better than that of MmNi without antimony atoms. 4.7 Co 0.12 Mn 0.2 Al 0.3 Rare earth hydrogen storage alloy materials, which fully proves that antimony atom coating effectively improves the low temperature MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 The specific surface area and pore size of rare earth hydrogen storage alloy materials broaden the transmission channel of hydrogen atoms, improve the transmission kinetics of hydrogen atoms, and thus greatly improve the MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 The low temperature discharge performance of rare earth hydrogen storage alloy materials. Therefore, the present invention has more advantages in commercial promotion.
[0046] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a rare earth hydrogen storage alloy, characterized in that: include: (1) dispersing Mm-Ni based rare earth hydrogen storage alloy particles in ethanol and stirring uniformly to obtain a mixed turbid liquid; (2) Antimony trichloride is dissolved in the mixed turbid liquid, and the mixture is allowed to stand after continuous stirring to obtain a mixture, which is then centrifuged, washed and vacuum dried in sequence to obtain a rare earth hydrogen storage alloy coated with antimony atoms.
2. The preparation method according to claim 1, characterized in that: (1) The particle size of the Mm-Ni based rare earth hydrogen storage alloy particles is 200 to 400 mesh.
3. The preparation method according to claim 1, characterized in that: (1) The Mm-Ni based rare earth hydrogen storage alloy is MmNi 4.7 Co 0.12 Mn 0.2 Al 0.3 , wherein Mm is composed of La and Ce in an atomic ratio of 0.78~0.84:0.18~0.
30.
4. The preparation method according to claim 1, characterized in that: (2) The concentration of antimony trichloride in the obtained mixture is 0.01 to 1 mol / L.
5. The preparation method according to claim 1, characterized in that: (2) The mass ratio of antimony trichloride to Mm-Ni based rare earth hydrogen storage alloy in the obtained mixture is 0.1-1:1-4.
6. The preparation method according to claim 1, characterized in that: (2) The stirring time is 10 to 48 hours and the standing time is 5 to 10 minutes.
7. The preparation method according to claim 1, characterized in that: (2) The washing solvents are deionized water and ethanol.
8. The preparation method according to claim 1, characterized in that: (2) The temperature of medium vacuum drying is 40-60°C, and the insulation time is 5-15 hours.
9. A rare earth hydrogen storage alloy prepared by the method according to any one of claims 1 to 8.
10. An application of the rare earth hydrogen storage alloy according to claim 9, characterized in that: Used as hydrogen storage alloy negative electrode for nickel-hydrogen batteries.
Citation Information
Patent Citations
Metal-organic framework compound in-situ coated hydrogen storage alloy negative electrode for nickel-metal hydride battery and preparation method of metal-organic framework compound in-situ coated hydrogen storage alloy negative electrode
CN114023927A
Two-dimensional layered antimony negative electrode material, two-dimensional antimonene material and preparation method and application thereof
CN114472902A
Three-dimensional cluster antimony material and preparation method and application thereof
CN114927676A
Lithium ion battery negative electrode material beta-SnSb / HCS / C and preparation method thereof
CN115332512A
Electrode of hydrogen storage alloy for alkaline storage battery
JP1991280357A